Etnobotani Tumbuhan Obat Tradisional untuk Mengatasi Hipertensi oleh Etnik Melayu Mulia Kerta Ketapang - Nurfitri, Hany; Syamswisna, Syamswisna; Titin, Titin (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
The rich flora of Indonesia plays a significant role in the lives of its people, particularly in health. The Mulia Kerta Ketapang Melayu ethnic group is one community that utilizes herbs for traditional medicine, especially for treating hypertension, a common condition in society. Knowledge of plant use for traditional hypertension medicine is passed down orally from generation to generation, resulting in a lack of proper documentation. This research aimed to document the plant species, identities, parts used, and procedures for utilizing plants as hypertension medicine by the Mulia Kerta Ketapang Melayu ethnic group. This study is a qualitative descriptive research employing triangulation methods (interviews, observation, and documentation) and plant identification as the primary data collection tools. The results of the study identified 33 plant species used as traditional hypertension medicine. Plants from the Rutaceae and Lamiaceae families were the most commonly utilized, each accounting for 9% of the species. Leaves were the most frequently used plant part, constituting 43.2%, while the boiling method was the most commonly employed preparation technique, used in 58% of cases. The findings of this research can serve as a reference for further studies and as a basis for comparing the similarities or connections between the Mulia Kerta Ketapang Melayu ethnic group and other ethnic groups in their use of traditional medicinal plants.